2003
DOI: 10.1353/dem.2003.0019
|View full text |Cite
|
Sign up to set email alerts
|

Economic potential and entry into marriage and cohabitation

Abstract: This article explores the relationship between economic potential and rates of entry into marriage and cohabitation. Using data from the 1990 census and the 1980-1992 High School and Beyond (Sophomore Cohort), we developed a method for explicitly estimating five time-varying measures of earnings potential. The analyses of union formation are based on an intergenerational panel study of parents and children, to which our measures of earnings potential were appended. The results indicate that all five measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
179
0
13

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(201 citation statements)
references
References 35 publications
9
179
0
13
Order By: Relevance
“…While there is a strong reciprocal link between marriage and employment, this link is less clear for cohabitation: the entry into cohabitation is less sensitive to employment status than the entry into marriage. In part these findings mirror those of earlier studies that find that men's economic characteristics are more important for the entry into marriage than for the entry into cohabitation (Bracher and Santow 1998;Oppenheimer 2003;Xie et al 2003;Sassler and Goldscheider 2004). We emphasize however that, though employment effects are weaker on entry into cohabitation, they are still strong and statistically significant.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…While there is a strong reciprocal link between marriage and employment, this link is less clear for cohabitation: the entry into cohabitation is less sensitive to employment status than the entry into marriage. In part these findings mirror those of earlier studies that find that men's economic characteristics are more important for the entry into marriage than for the entry into cohabitation (Bracher and Santow 1998;Oppenheimer 2003;Xie et al 2003;Sassler and Goldscheider 2004). We emphasize however that, though employment effects are weaker on entry into cohabitation, they are still strong and statistically significant.…”
Section: Discussionsupporting
confidence: 85%
“…Cohabitation can therefore be used as a way for couples to reduce uncertainty, before marriage, about future career prospects. Recent American evidence does suggest that economic prospects are less important for entry into cohabitation, although it is less clear whether favourable economic prospects among men also have a positive effect on the transition from cohabitation to marriage (Liefbroer 1991;Smock and Manning 1997;Bracher and Santow 1998;Kravdal 1999;Brown 2000;Oppenheimer 2003;Sassler and McNally 2003;Xie et al 2003).…”
Section: Hypotheses About the Effects Of Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using either cross-sectional or longitudinal data have invariably observed a positive relationship between measures of men's economic prospects and marriage formation (e.g. Cooney and Hogan 1991;Goldscheider and Waite 1986;Goldstein and Kenney 2001;Lloyd and South 1996;MacDonald and Rindfuss 1981;Mare and Winship 1991;Oppenheimer, Kalmijn, and Lim 1997;Qian and Preston 1993;Sassler and Schoen 1999;Sweeney 2002;Teachman, Polonko, and Leigh 1987;Xie et al 2003). The uniformity in this finding confirms the traditional model of marriage in which the husband is considered the breadwinner and the wife the homemaker.…”
Section: Theoretical Issues and Previous Studiessupporting
confidence: 55%
“…As a result, education, representing economic potential (Xie et al 2003), is a major resource in the marriage market that speeds up marriage. In East Asian countries, universal and early marriage has long been practiced (Thornton and Lin 1994).…”
Section: Cohort Comparisonsmentioning
confidence: 99%